2018
DOI: 10.1152/ajpgi.00311.2017
|View full text |Cite
|
Sign up to set email alerts
|

Bile acid profiles within the enterohepatic circulation in a diabetic rat model after bariatric surgeries

Abstract: Bile acids (BAs), which are synthesized in the liver and cycled in the enterohepatic circulation, have been recognized as signaling molecules by activating their receptors in the intestine and liver. Serum taurine-conjugated BAs have been shown to be elevated after bariatric surgeries although the postoperative BA profiles within the enterohepatic circulation have not been investigated. Clarification of these profiles could help explain the mechanisms by which bariatric surgery leads to BA profile alterations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 63 publications
0
10
0
1
Order By: Relevance
“…acid levels were increased in rats that underwent bariatric surgery [21]. The decrease in body weight or impairment of body weight gain might contribute to the increase in TBA levels.…”
Section: Plos Onementioning
confidence: 94%
“…acid levels were increased in rats that underwent bariatric surgery [21]. The decrease in body weight or impairment of body weight gain might contribute to the increase in TBA levels.…”
Section: Plos Onementioning
confidence: 94%
“…In addition, emerging evidence indicates that bile acids (BAs) play a key role in the mechanisms of bariatric surgery. 8,9 BAs are cholesterolderived molecules and aid in the absorption of dietary fat. BAs, as ligands for the nuclear farnesoid X receptor (FXR), control their own synthesis and hepatic lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, after weight-loss surgery in patients with T2DM, blood glucose levels, insulin resistance and serum bile acid levels were all improved. [37][38][39][40] All of which indicated that bile acids can be potentially used as therapeutic targets for treating T2DM.…”
Section: Discussionmentioning
confidence: 99%